Analysis of the Role of Berkah Garbage Bank on the Economic Income of the Community In Belawan Universitas Pembangunan Panca Budi - Yanti Br Naibaho; Annisa Ilmi Faried (Journal of Research in Social Science and Humanities, 2025)
This study examines the role of Bank Sampah Berkah (BSB) in Belawan, Medan, in addressing waste management issues while simultaneously improving the economic well-being of the community. Prior to BSB's establishment in 2016, the majority of Belawan residents (76.2%) disposed of waste indiscriminately, resulting in high daily waste generation (6 kg by 32 respondents, 4–6 kg by 42 respondents). BSB's presence significantly altered this behavior, evidenced by the elimination of respondents generating 6 kg of waste and a drastic increase in the group producing less than 3 kg of waste (rising to 40 respondents). The research findings indicate increased public awareness and participation in waste sorting, driven by direct financial benefits from waste savings (estimated average IDR 200,000/month per customer). These funds are utilized for basic needs, children's education, and even business capital. Although BSB manages a smaller volume of waste (9,245.64 kg/year) compared to Bank Sampah Unit Tri Golan Jaya (148,560 kg/year), BSB excels in its measurable and significant microeconomic impact on its customers. Bank Sampah Berkah proves to be an effective model for community-based waste management that empowers the economy, despite facing challenges of fluctuating customer participation and limited access to recycling product markets.